2015
DOI: 10.3109/0284186x.2015.1102321
|View full text |Cite
|
Sign up to set email alerts
|

Should breathing adapted radiotherapy also be applied for right-sided breast irradiation?

Abstract: Background: Voluntary moderate deep inspiration breath-hold (vmDIBH) is widely used for left sided breast cancer patients. The purpose of this study was to investigate the usefulness of vmDIBH in local and locoregional radiation therapy (RT) of right-sided breast cancer. Materials and Methods: For fourteen right-sided breast cancer patients, 3D-conformal (3D-CRT) RT plans (i.e., forward IMRT) were calculated on free-breathing (FB) 3D-CRT(FB) and vmDIBHCT-scans, for local-as well as locoregional breast treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…The findings between FB right-sided and FB left-sided versus RG left-sided treatments were identical in the two arms as expected. For rightsided treatment plans Essers et al reported no gain from RG for breast only RT considering dose to OAR [24]. This supports the usefulness of considering FB right-sided treatment plans as the control group.…”
Section: Discussionmentioning
confidence: 85%
“…The findings between FB right-sided and FB left-sided versus RG left-sided treatments were identical in the two arms as expected. For rightsided treatment plans Essers et al reported no gain from RG for breast only RT considering dose to OAR [24]. This supports the usefulness of considering FB right-sided treatment plans as the control group.…”
Section: Discussionmentioning
confidence: 85%
“…The primary aim of our study was to assess the dosimetric benefits of DIBH compared to standard free breathing (FB) approaches in terms of liver doses for RBC patients following mastectomy. Previous studies exclusively focused on patients with LBC, and just two recent studies have examined the benefit and applicability of DIBH in patients with RBC [9,10]. Although these studies provide evidence in this field, they are not without shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies provide evidence in this field, they are not without shortcomings. Firstly, liver doses were not addressed by Essers et al [9] in the first study. Another study that provided dosimetric comparison of liver doses between the techniques was conducted on LBC patients, as intact right breast was assumed to be representative of breast-conserving surgery for dosimetry purposes [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Leveraging the inherent stability of DIBH can reduce cranio-caudal intrafraction hepatic motion from 19mm to 1-5mm, 25,26 reduce liver volume by 63% (134cm 3 to 50cm 3 ) and mean liver dose by 46% (from 4.8 to 2.6 Gy) compared to a free breathing plan 10 and deliver superior ipsilateral and total lung dosimetry. 27,28 The range of maximum liver dose in the current study was surprisingly large for left-sided treatments. Median data confirmed the phenomena of liver irradiation was negligible for all but one participant, who had a medially-placed tumour, a high BMI and SCF irradiation that exaggerated inferior beam divergence for tangential fields.…”
Section: Discussionmentioning
confidence: 67%